Integrated Analysis of the Clinical and Molecular Characteristics of IDH Wild-Type Gliomas in the Chinese Glioma Genome Atlas - Wang, Peng; Liu, Yanwei; Zhi, Lin; Qiu, Xiaoguang (Frontiers in Oncology, 2021)
Purpose: Current studies and guidelines suggest that the biobehavior of IDH-wild type (IDH-wt) lower-grade glioma (LGG, WHO II-III) is similar to IDH-wt glioblastoma (GBM). However, differences in their clinical and molecular characteristics have not been reported. This study aimed to analyze the clinical and genetic information of gliomas with IDH-wt. Methods: Four hundred patients with IDH-wt were enrolled in the study (LGG=165, GBM=224), and their clinical and genetic information was collected from the Chinese Glioma Genome Atlas (CGGA). We conducted an analysis of this information between the two groups of patients and drew conclusions thereof. Results: The median age of the LGG patients was 42 (14-74) years, while that of the GBM patients was 51 (14-79) years (P<0.010). GBM patients were more likely to undergo total resection (P=0.018) and had fewer epileptic seizure symptoms (P<0.001). The median overall survival (OS) was 48.13 months for the LGG patients and only 14.5 months for the GBM patients (P<0.01). The median progression-free survival (PFS) was 33.1 months for the LGG patients and only 9.3 months for the GBM patients (P<0.01). GBM patients were more prone to PETN mutations (P=0.010). Transcriptome analysis showed that the differentially expressed genes in LGG patients were mainly enriched in metabolic pathways and pathways in cancer and in the function of signal transduction and positive regulation of GTPase activity, while in GBM patients, they were mainly enriched in the PI3K-Akt signaling pathway and in the functions of apoptotic process and oxidation-reduction process. Conclusions: Our data indicate that these two groups of patients should be re-evaluated and treated differently, despite both having IDH wild type.